2017
DOI: 10.1002/kin.21087
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Kinetics Study on the Intramolecular Hydrogen Shift Reactions of Alkylperoxy Radicals in 2‐Methyltetrahydrofuran Oxidation

Abstract: 2‐Methyltetrahydrofuran (2‐MTHF) is one of the potential fuel components based on its combustion behavior, engine efficiency, and emission performance as proposed by the Cluster of Excellence “Tailor Made Fuels from Biomass (TMFB)” at RWTH Aachen University, Germany. Reaction kinetics of intramolecular hydrogen shift (ROO to QOOH) reactions in 2‐MTHF is theoretically investigated in this work. High‐pressure limit rate constants (500–2000 K) are determined from the transition state theory by employing the CBS‐Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The variations in the structure between THF and 2,5-DMTHF required modification of the activation energy of -2 kcal/mol in the case of a tertiary carbon and +2 kcal/mol for a primary carbon bonded to the eliminated H atom [8]. The reaction rate coefficients for isomerization reactions of RȮ 2 into Q OOH were taken from the work of Parab et al [38], calculated for 2-MTHF. Analogies with the reaction rate coefficients used for the model of THF [5] were adopted for the reactions of hydroperoxyl radical elimination from Q OOH, formation of a cyclic ether and ȮH radical, beta-scission of Q OOH radical, and molecular rearrangement forming a dioxene molecule and an ȮH radical.…”
Section: Low Temperature Model For 25-dmthfmentioning
confidence: 99%
“…The variations in the structure between THF and 2,5-DMTHF required modification of the activation energy of -2 kcal/mol in the case of a tertiary carbon and +2 kcal/mol for a primary carbon bonded to the eliminated H atom [8]. The reaction rate coefficients for isomerization reactions of RȮ 2 into Q OOH were taken from the work of Parab et al [38], calculated for 2-MTHF. Analogies with the reaction rate coefficients used for the model of THF [5] were adopted for the reactions of hydroperoxyl radical elimination from Q OOH, formation of a cyclic ether and ȮH radical, beta-scission of Q OOH radical, and molecular rearrangement forming a dioxene molecule and an ȮH radical.…”
Section: Low Temperature Model For 25-dmthfmentioning
confidence: 99%
“…• Reaction rate constants for the RȮ 2 to QOOH isomerization type of reactions (class 15) were adopted from the theoretical study of Parab et al [35]. These rate parameters were calculated for all sites of 2-MTHF at CBS-QB3 level of theory.…”
Section: General Model Featuresmentioning
confidence: 99%
“…The study compared the rate constants of ROO isomers of 3-MTHF with their counterparts of methylcyclopentane, which revealed that faster kinetics in 3-MTHF can be attributed to the effect of ring O 2 on the intramolecular hydrogen shift reactions. A similar approach was employed by Parab et al [131], where the most important abstraction sites were found to be carbon sites neighboring a ring oxygen atom, which was linked to weak C-H bond. Furthermore, Sudholt et al [28] calculated the BDEs of a number of THFs and explored the initial reactions during the auto-ignition for these fuels.…”
Section: Quantum Chemical Kinetic Calculationsmentioning
confidence: 95%
“…Tetrahydrofurans were the focus of another group of computational chemical kinetic studies [26,28,[129][130][131][132]. For instance, the study by Simmie [26] presented calculations of the entropies, enthalpies of formation, enthalpy functions, specific heats (c p ) and all C-H and C-CH 3 BDEs for THF, 2-MTHF and 2,5-dimethyltetrahydrofuran (DMTHF).…”
Section: Quantum Chemical Kinetic Calculationsmentioning
confidence: 99%